Oxidation of benzyl alcohol by pyridinium dichromate in acetonitrile. Using the para/meta ratio of substituent effects for mechanism elucidation - Kabilan, S (2015)
Rate constants were measured for the oxidation reaction of benzyl alcohol and twenty-five ortho-, meta- and para-monosubstituted derivatives in the temperature range 293-323 K at intervals of 10 K. The kinetics were followed spectrophotometrically in dry acetonitrile acidified with trichloroacetic acid (TCA) using pyridinium dichromate (PDC) as oxidising agent under pseudo-first-order conditions with respect to PDC. Benzaldehyde is the only oxidation product and no reaction takes place without TCA. From good linear Eyring plots activation enthalpies Delta(double dagger)H(o) and entropies Delta(double dagger)S(o) are calculated. For ortho- substituted benzyl alcohols high Delta(double dagger)H(o) values and small negative Delta(double dagger)S(o) values point to an ortho effect on the rate-determining step. Using the tetralinear approach to substituent effects, the average value (λ) over bar = 1.09 +/- 0.05 for the para/meta ratio of inductive or Electra effects is obtained and negative Hammett reaction constants decreasing in magnitude with increasing temperature are found. A mechanism implicating the prior acid-catalysed formation of neutral benzyl hydrogen dichromate ester followed by intramolecular proton transfer is proposed. Modelling of parameter lambda in terms of the electrostatic theory showed its experimental value to be consistent with the ratio of electric potentials generated in the immediate vicinity of the nearest chromium atom by dipolar substituents introduced in the aromatic ring on para and meta positions. At a molecular level the oxidative, rate-determining step is suggested to be triggered by the retraction or shrinkage of electron pairs from sigma bonds in Cr-2(VI) species to non-bonding orbitals in unstable Cr-IV-O-Cr-VI species. In contrast with past interpretations, an electrochemical approach is used to explain negative values for the Hammett reaction constant.